2020
DOI: 10.1111/acel.13183
|View full text |Cite
|
Sign up to set email alerts
|

Liver osteopontin is required to prevent the progression of age‐related nonalcoholic fatty liver disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
2
12
0
1
Order By: Relevance
“…Our in vivo results from HFD-challenged mice and in vitro evidence from cultured preosteoclasts showed that senescent preosteoclasts secrete previously identified common SASP factors, such as IL-1β, IL-6, VEGF, and OPN (32,(68)(69)(70), as well as several factors that were not previously recognized in SnCs, including Lipocalin-2, Resistin, Cystatin C, IL-33, CCN4, MPO, and PDGF-BB. Importantly, the abnormally high production of these factors in the subchondral bone of HFDchallenged mice is fully or partially rectified by deletion of p16 from preosteoclasts.…”
Section: Discussionsupporting
confidence: 52%
“…Our in vivo results from HFD-challenged mice and in vitro evidence from cultured preosteoclasts showed that senescent preosteoclasts secrete previously identified common SASP factors, such as IL-1β, IL-6, VEGF, and OPN (32,(68)(69)(70), as well as several factors that were not previously recognized in SnCs, including Lipocalin-2, Resistin, Cystatin C, IL-33, CCN4, MPO, and PDGF-BB. Importantly, the abnormally high production of these factors in the subchondral bone of HFDchallenged mice is fully or partially rectified by deletion of p16 from preosteoclasts.…”
Section: Discussionsupporting
confidence: 52%
“…( 36 ) OPN plays a role in the progression of nonalcoholic steatohepatitis (NASH) by inhibiting autophagy ( 37 ) and increasing hepatocyte senescence. ( 38 )…”
Section: Opn and Hepatic Steatosismentioning
confidence: 99%
“…ER stress is also involved in the progression of senescence in osteoarthritic chondrocytes, accompanied by increased SA-β-galactosidase activity [151]. A recent study in mice and patients showed that NAFLD was associated with increased expression of senescence markers in the liver, and that senescence correlated with increased lipid accumulation and increased ER stress, demonstrated by increased phosphorylation of eIF2a and IRE1a [152]. Therefore, ER stress is very likely to contribute to the induction of cellular senescence during NAFLD.…”
Section: Senescence and Er Stressmentioning
confidence: 99%